Basic electronics - Holbrook, Harold D.; Seeley, Walter J. (Walter James), 1894- (New York : Pergamon Press, 1971)
Basic Electronics is an elementary text designed for basic instruction in electricity and electronics. It gives emphasis on electronic emission and the vacuum tube and shows transistor circuits in parallel with electron tube circuits. This book also demonstrates how the transistor merely replaces the tube, with proper change of circuit constants as required. Many problems are presented at the end of each chapter. This book is comprised of 17 chapters and opens with an overview of electron theory, followed by a discussion on resistance, inductance, and capacitance, along with their effects.
Front Cover; Basic Electronics; Copyright Page; Tabel of Contents; Introduction; Chapter 1. ELECTRON THEORY; 1-1 THE ATOM; 1-2 ELECTRON THEORY OF MATTER; 1-3 CONDUCTORS AND INSULATORS; 1-4 METHODS OF FREEING ELECTRONS FROM SURFACES OF MATERIALS; 1-5 CHARGES AND FIELDS; 1-6 DIRECT AND ALTERNATING CURRENT; 1-7 CURRENT SOURCES; 1-8 SOURCES AND SYMBOLS; Questions and Problems; Chapter 2. RESISTANCE; 2-1 CONCEPT OF RESISTANCE; 2-2 RESISTANCE AND LENGTH; 2-3 RESISTANCE AND CROSS-SECTIONAL AREA; 2-4 RESISTANCE AND MATERIAL; 2-5 RESISTANCE AND TEMPERATURE; 2-6 RESISTANCE AND CIRCUIT POWER. 2-7 RESISTANCES IN SERIES AND PARALLELQuestions and Problems; Chapter 3. INDUCTANCE; 3-1 INDUCTANCE DEFINITION AND DISCUSSION OF REACTANCE; 3-2 FACTORS AFFECTING INDUCTANCE; 3-3 INDUCTANCE COILS AND Q; 3-4 COIL DESIGN; 3-5 INDUCTANCES IN SERIES AND PARALLEL; 3-6 TRANSFORMERS; 3-7 TRANSFORMER EFFICIENCY AND ACTION; Questions and Problems; Chapter 4. CAPACITANCE; 4-1 CAPACITANCE AND CAPACITIVE REACTANCE; 4-2 FACTORS AFFECTING CAPACITANCE; 4-3 THE Q OF A CAPACITOR; 4-4 CAPACITORS IN SERIES AND PARALLEL; 4-5 CLASSIFICATION OF CAPACITORS; 4-6 SPECIAL CAPACITORS AND APPLICATIONS. Questions and ProblemsChapter 5. BASIC R-L-C CIRCUITS; 5-1 INTRODUCTION TO IMPEDANCE AND FACTORS AFFECTING IMPEDANCE; 5-2 IMPEDANCE AND PHASE; 5-3 IMPEDANCES IN SERIES; 5-4 IMPEDANCES IN PARALLEL; 5-5 IMPEDANCE MATCHING; Questions and Problems; Chapter 6. ELECTRONICS AND ELECTRON TUBES; 6-1 GENERAL DISCUSSION; 6-2 THERMIONIC EMISSION; 6-3 THE DIODE; 6-4 THE TRIODE; 6-5 THE TETRODE; 6-6 THE PENTODE; 6-7 DIODE, TRIODE, TETRODE, PENTODE; 6-8 INTERELECTRODE CAPACITANCE; 6-9 TUBES, FREQUENCIES, AND CLASSIFICATIONS; 6-10 MULTIPURPOSE TUBES; 6-11 SPECIAL INDICATING TUBES; Questions and Problems. Chapter 7. SEMICONDUCTORS AND TRANSISTORS7-1 SEMICONDUCTORS; 7-2 P-N JUNCTION; 7-3 TRANSISTOR OPERATION; 7-4 TRANSISTOR ADVANTAGES; Questions and Problems; Chapter 8. BASIC ELECTRONIC CIRCUITS; 8-1 BLOCK DIAGRAMS; 8-2 CIRCUIT DETAILS; 8-3 POWER LEVELS FOR TUBES AND TRANSISTORS; 8-4 BIAS; 8-5 METHODS OF COUPLING; 8-6 CIRCUIT CONFIGURATIONS; Questions and Problems; Chapter 9. TUNED CIRCUITS; 9-1 BASIC TUNED CIRCUITS; 9-2 SERIES TUNED CIRCUIT; 9-3 ANALYSIS OF A SERIES TUNED CIRCUIT; 9-4 PARALLEL TUNED CIRCUITS; 9-5 ANALYSIS OF A PARALLEL TUNED CIRCUIT; 9-6 TRAPS AND TUNED CIRCUITS IN COMBINATION. 9-7 DISCUSSION AND APPLICATION OF TUNED CIRCUITSQuestions and Problems; Chapter 10. BASIC AMPLIFIER CIRCUITS; 10-1 AMPLIFIER CIRCUIT FUNDAMENTALS; 10-2 VOLTAGE AND POWER AMPLIFIERS; 10-3 CLASS ""A"" OPERATION; 10-4 CLASS ""B"" OPERATION; 10-5 CLASS ""C"" OPERATION; 10-6 NARROW BAND AMPLIFIERS AND DISTORTION; 10-7 BROAD BAND AMPLIFIERS; Questions and Problems; Chapter 11. BASIC OSCILLATOR CIRCUITS; 11-1 OSCILLATION EXPLAINED; 11 -2 BASIC TYPES OF OSCILLATORS; 11-3 FREQUENCY MULTIPLICATION; 11-4 HETERODYNING; 11-5 SPECIAL OSCILLATOR CIRCUITS; 11 -6 SPECIAL OSCILLATOR DEVICES.
MNS
Development Book Agency
Keywords: Electronics